The soviet project for high school: reaching autonomy - Viktor Adamskyi (Pedagogical Discourse, 2007)
The author of the article researches the problem of realization of basis of administrative autonomy of high school in theconditions of soviet reality on the example of public election of the rector of Kam’yanets’-Podil’s’kyi institute of public educationin 1922.